2009
DOI: 10.1021/ed800008g
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of Oxygen Investigated with Easily Accessible Instrumentation

Abstract: The physical properties of oxygen, in particular, the blue color of the liquid phase, the red glow of its chemiluminescence, and its paramagnetism as shown by the entrapment or deflection of liquid oxygen by a magnetic field, can be investigated in a regular school setting with hand-held spectrophotometers and digital cameras. In college-level chemistry courses, the paramagnetic property often serves as a dramatic illustration of the usefulness of molecular orbital (MO) theory. However, MO treatment of oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…Porphyrins and their metal complexes are well known as highly effective triplet state photosensitizers to be capable of producing singlet molecular oxygen, 1 O 2 ( 1 D g ), under illumination in the presence of oxygen. [9][10][11][12][13][14][15][16][17][18] Singlet oxygen is a highly reactive and electrophilic species that reacts with an electron-rich moiety, such as the double bond of ascorbate. [33][34][35] Although a number of studies have so far reported on the production of singlet oxygen molecules through the photo-excitation of porphyrins, [9][10][11][12][13][14][15][16][17][18] molecular level elucidation about how triplet oxygen interacts with porphyrins remains unsolved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Porphyrins and their metal complexes are well known as highly effective triplet state photosensitizers to be capable of producing singlet molecular oxygen, 1 O 2 ( 1 D g ), under illumination in the presence of oxygen. [9][10][11][12][13][14][15][16][17][18] Singlet oxygen is a highly reactive and electrophilic species that reacts with an electron-rich moiety, such as the double bond of ascorbate. [33][34][35] Although a number of studies have so far reported on the production of singlet oxygen molecules through the photo-excitation of porphyrins, [9][10][11][12][13][14][15][16][17][18] molecular level elucidation about how triplet oxygen interacts with porphyrins remains unsolved.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] Singlet oxygen is a highly reactive and electrophilic species that reacts with an electron-rich moiety, such as the double bond of ascorbate. [33][34][35] Although a number of studies have so far reported on the production of singlet oxygen molecules through the photo-excitation of porphyrins, [9][10][11][12][13][14][15][16][17][18] molecular level elucidation about how triplet oxygen interacts with porphyrins remains unsolved. To clarify this problem, we studied the interaction mechanism between the TiO(tpyp) complex and triplet oxygen molecule from the viewpoint of molecular orbital characteristics and potential energy changes based on the computed results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The red light emitted by singlet molecular oxygen is a standard textbook example of chemiluminescence, , and has a long history of experimental and theoretical , investigations. The energy of the strongest band of the emitted light is approximately twice as large as that of the vertical O 2 ( a 1 Δ g ) → O 2 ( X 3 ∑ g – ) transition, which is spin-forbidden.…”
mentioning
confidence: 99%
“…In case of the emission, however, the mechanism does not seem to be proven yet. Kasha in his classic paper speaks about a vaguely defined “simultaneous transition” of a pair of molecules, and many authors believe that the emission comes from dimers even at room temperature . Billington argues that dimers would not exist above 100 K, and proposes the emission to be collision induced (CIE).…”
mentioning
confidence: 99%